Ibis M2016: a bread wheat variety with medium-strong gluten for El Bajío, Mexico - Ledesma-Ramírez, Lourdes; Solís-Moya, Ernesto; Mariscal-Amaro, Luis Antonio; Buenrostro-Rodríguez, Juan Francisco; Héctor Eduardo; Huerta-Espino, Julio (Revista Mexicana de Ciencias Agrícolas, 2024)
The Ibis M2016 variety is a bread wheat variety with medium-strong gluten that was obtained in the Wheat Genetic Improvement Program of the Bajío Experimental Field by hybridization through a simple cross between the Colibri and Finsi genotypes; its selection history is TC070080-2R-0C-0R-1CSE-0R. In plots of producers from El Bajío, it surpassed Cortazar S94 in grain yield by 23.8% and the varieties Alondra F2014, Luminaria F2012, Bárcenas S2002, Maya S2007, and Urbina S2007 by 3.4, 45.7, 41, 21.4, and 18.7%, respectively. It is moderately resistant to yellow rust; when Cortazar S94 reached 40% damage from the disease, Ibis M2016 showed damage ranging from 10 to 15%. The variety was developed from 2007, when the cross was made; in 2021, it was released as a commercial variety. Ibis M2016 was made available to producers to meet the demand for varieties with medium-strong gluten, resistant to rust, and with yields higher than those of commercial varieties. Ibis M2016 is recommended for sowing in the El Bajío region, which had altitudes of 1 500 to 1 800 m and includes part of the states of Guanajuato, Michoacán, Jalisco and Querétaro.
Keywords: gluten; resistance; yield